(NsWQTO OB(B')QÃ(NDNANNQ uKRAÇNI (B((NDO RÆ^NICÆ aKTU zLUKI unr Æ zunr(B) /s)E - (NlITWIN(B, (Nw(B. (Nm(B.,s; (NkOPILENKO(B, (No(B. (Nl(B.,s; (NmI]AK(B, )Qæ. (Nm(B.,s)E; )Qæ(NNSTITUT ZAKONODAWSTWA wERHOWNOÇ rADI uKRAÇNIs)E ((NkI)QÇW (B:s)E (NpARLAMENTSXKE WIDAWNICTWO(B,s, 2012)
(Nu WIDANN)QÆ WIKORISTANÆ GAZETNÆ PUBLÆKACÆÇ(B, (N]O ZBERÆGA@TXSQ U FONDAH DERVAWNOÇ NAUKOWOÇ ARHÆWNOÇ BÆBLÆOTEKI (B((NM(B. (NkIÇW(B).s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NdERVAWNE PRAWOs -- (NaKT zLUKIs -- (NuKRA)QÇNAs)E -- 20 (NST(B.s